2011
DOI: 10.1371/journal.pone.0022705
|View full text |Cite
|
Sign up to set email alerts
|

sTarPicker: A Method for Efficient Prediction of Bacterial sRNA Targets Based on a Two-Step Model for Hybridization

Abstract: BackgroundBacterial sRNAs are a class of small regulatory RNAs involved in regulation of expression of a variety of genes. Most sRNAs act in trans via base-pairing with target mRNAs, leading to repression or activation of translation or mRNA degradation. To date, more than 1,000 sRNAs have been identified. However, direct targets have been identified for only approximately 50 of these sRNAs. Computational predictions can provide candidates for target validation, thereby increasing the speed of sRNA target iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 43 publications
(66 reference statements)
1
67
0
Order By: Relevance
“…mRNA target genes of sRNAs were predicted from the A. fabrum C58 genome (accession number NC_003062, NC_003063, NC_003064, and NC_003065) using IntaRNA (Busch et al 2008), sTarPicker (Ying et al 2011), and RNApredator (Eggenhofer et al 2011) algorithms. We arbitrarily selected the 350 most significant mRNA targets provided by each algorithm.…”
Section: Determination Of 59 and 39 Ends By Race-pcrmentioning
confidence: 99%
“…mRNA target genes of sRNAs were predicted from the A. fabrum C58 genome (accession number NC_003062, NC_003063, NC_003064, and NC_003065) using IntaRNA (Busch et al 2008), sTarPicker (Ying et al 2011), and RNApredator (Eggenhofer et al 2011) algorithms. We arbitrarily selected the 350 most significant mRNA targets provided by each algorithm.…”
Section: Determination Of 59 and 39 Ends By Race-pcrmentioning
confidence: 99%
“…Target genes of QfsR were predicted from the A. fabrum C58 genome using IntaRNA (Busch et al ., ), sTarPicker (Ying et al ., ) and RNApredator (Eggenhofer et al ., ) algorithms. Targets of interest were selected as previously described (Dequivre et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Predicting the mRNA targets of QfsR would provide clues for identifying its cellular function. We applied a combination of three algorithms (RNApredator, sTarPicker and IntaRNA) (Busch et al, 2008;Eggenhofer et al, 2011;Ying et al, 2011;Dequivre et al, 2015) and selected the 54 genes jointly identified by them. These candidates were homogeneously distributed among the four replicons, i.e., the circular and linear chromosomes and AtC58 and TiC58 plasmids (Supporting Information Table S2).…”
Section: Qfsr Is Predicted To Interact With Several Polycistronic Mrnmentioning
confidence: 99%
“…An sRNA target prediction web server on top of RNAplex is implemented by the software RNApredator 115 . The web server sTarPicker combines ideas from accessibility-based and concatenation-based approaches 118 . Putative seed interactions are extended by computing a joint secondary structure of sRNA and mRNA.…”
Section: Rna-rna Interactionsmentioning
confidence: 99%